Therapeutic utilization of zinc supplementation concurrent with ozone therapy ameliorates diabetic foot ulcer and attenuates serum level of C-reactive protein- A case report study - Reza Dadfar; Layasadat Khorsandi; Reza Goujani; Seyyed Farid Mousavi; Zahra Aslani (Advanced Biomedical Research, 2023)
Non-healing diabetic foot ulcer (DFU) is one of the main complications in diabetic patients. This case reported a 65-year-old male with a neuropathic ulcer in the right foot came to Ahwaz Wound Clinic after the wound had not healed with routine treatments. In addition to the routine treatment program, we used tropical ozone therapy and autohemotherapy (blood ozone therapy) for 2 months. Zinc supplementation (50 mg) was also administered daily during the treatment. The DFU was clearly healed with diminishing inflammation and wound closing, and there were no side effects. Additionally, the C-reactive protein level was obviously decreased during the treatment indicating effective suppression of infection. This way indicates a helpful new intervention approach to the treatment of DFU.